The Efficacy of Sodium Bisulfate Salt (SBS) Alone and Combined With Peracetic Acid (PAA) as an Antimicrobial on Whole Chicken Drumsticks Artificially Inoculated With Salmonella Enteritidis - Dittoe, Dana K.; Atchley, Julie A.; Feye, Kristina M.; Lee, Jung Ae; Knueven, Carl J.; Ricke, Steven C. (Frontiers in Veterinary Science, 2019)
The presence of Salmonella spp. on poultry products is one of the leading causes of foodborne illness in the United States. Therefore, novel antimicrobial substances are being explored as potential interventions in poultry processing facilities. The objective of the current study was to evaluate the efficacy of varying concentrations of sodium bisulfate salt, SBS, alone or in combination with peracetic acid, PAA, in 15 s whole part dips. 96 drumsticks (4 replications, 8 treatments, 3 days) were inoculated separately in a 400 mL solution of nalidixic resistant (NA) Salmonella Enteritidis (107 CFU/mL) and allowed to adhere for 60 to 90 min at 4 °C for a final concentration of 106 CFU/g. The experimental treatments included: a no treatment (control), and 15 s dips in 300 mL of tap water alone (TW) or with the addition of 1%; 2%; and 3% SBS; 1%; 2%; and 3% SBS+PAA. After treatment, drumsticks were stored at 4 °C until microbial sampling was conducted. On d 0, l and 3, drumsticks were rinsed in 150 mL of nBPW for 1 min, 100 μL of rinsate was serially diluted, spread plated on XLT4+NA (20 µg/mL), and incubated aerobically at 37 °C for 24 h. Log-transformed counts were analyzed using a randomized complete block design (day) using One-Way ANOVA, polynomial contrasts, and pairwise comparisons with means being separated by Tukey’s HSD with a significance level of P ≤ 0.05. A treatment by day interaction (P=0.14071) was not substantial. Thus, the treatment effect was investigated separately by days. Over time, a linear trend was observed in S. Enteritidis concentration when SBS was increased (1 < 2 < 3%). The concentration of S. Enteritidis was different between 1% SBS and 1% SBS+PAA on d 0. However, the level of S. Enteritidis was not different among drumsticks treated in 2 and 3% SBS and 2 and 3% SBS+PAA across d 0, 1, 3. The application of 3% SBS alone or in combination with 200 ppm of PAA is capable of reducing the presence of Salmonella over a 3-d refrigeration period; potentially increasing the safety of poultry products for consumers.